Synthesis and Characterization of Polyether Polyol Based on Epoxy Cyclohexane and Epichlorohydrin - Jinjie ZHANG; Yingping QI; Yinghua QIAO; Yongfeng SHEN; Hua LI (Medžiagotyra)
Epoxycyclohexane-epichlorohydrin polyether polyol was synthesized by using epoxy cyclohexane and epichlorohydrin as raw materials, glycerol as an initiator, dichloromethane as solvent and aluminum chloride as catalysis. The structure of the copolyether was characterized by infrared (IR) spectroscopy and nuclear magnetic resonance (NMR), and its viscosity was determined. The results showed that the structure and viscosity properties of the products prepared by using aluminum chloride as the catalyst and the boron trifluoride diethyl ether catalyst were basically the same, but the aluminum chloride was more environmentally safe and lower in cost. At the same time, the polyurethane coating film prepared by using the copolyether synthesized by using aluminum chloride as a catalyst had excellent performance.